Behaviours of methane and water in heterogeneous shale nanopores: Effect of water saturation and pore size. (1st March 2023) - Zhou, Jun; Zhang, Chengpeng; Ranjith, P.G.
Graphical abstract: Highlights: Structural features of methane/water two-phase in nanoslits are highly affected by pore size and surface wettability. Two-phase flow in 4.0 nm quartz nanoslits transits from annular flow to slug flow with increased water saturation. Methane and water phase flow jointly in 4.0 nm kerogen nanoslits for various water saturations. The flow rate of methane through 1.5 nm nanoslits is much slower than that through wider nanoslits. Abstract: Understanding the structure and flow behaviours of methane and water co-existing in shale nanopores is crucial for the optimal exploitation of shale reservoirs after hydro-fracking stimulation. In this study, a number of MD simulations are used to analyse the structure and flow pattern of such a two-phase fluid in quartz and kerogen nanoslits. Our findings indicate that water molecules preferentially adsorb near walls, generating water films and finally constructing a water bridge in quartz nanopores, but in kerogen nanopores they form a plug-like water cluster. As pore size decreases, both organic and inorganic nanoslits enclose increasingly complex water/methane complexes. For two-phase transport behaviour, methane flow has a parabolic profile with fading peaks as Sw increases, but water films near the wall of quartz nanopores appear to be static. In contrast, the methane and water phases flow jointly in kerogen nanopores for all Sw values. As methane primarily exists as an adsorption gas in both quartz and kerogen nanopores, its flow rate is further slowed by approximately-one order of magnitude in narrower nanoslits. Notably, the water restriction in organic pores is slightly weaker than that in quartz pores, around 10 % less in average flow velocity. Our findings will contribute to the advancement of numerical models of shale gas movement in wet shale reservoirs.